Proposta de livro didático para o estudo da dinâmica nos cursos técnicos: mecatrônica, eletrônica, eletrotécnica e áreas afins - Oliveira, Sidomar Pirrony Rodrigues de (2019)
Technological education has been growing in Brazil, as the market needs professionals that are appropriate to technological issues and companies are increasingly in need of increasingly capable technicians. The vocational technical courses have in their curriculum, Physics contents that are very important for a solid formation, so it is necessary a good understanding of these concepts and properties. This research proposes the elaboration of a textbook with a curricular organization directed to professional education. The methodology took place in three stages called: “The Teachers' Vision”, aiming to gather information from teachers about the difficulty that students, newcomers from elementary school II, present when studying the Electricity course. “Prior Knowledge” with the application of questionnaires to assess the prior knowledge that students bring from elementary school II in the Physical discipline, referring to the part of Mechanics as well as the part of Electricity and Magnetism. “Product Evaluation in the Students' Vision” using questionnaires to identify factors that may contribute to and hinder the teaching and learning process of Physics in the first year students of the integrated high school of Mechatronics, Electronics and related areas. Keywords: